INTERVIEW: Recognizing and Resisting False Prophets - Atwebembeire, Rodgers; ACFARvideo (2022)
What’s behind the plague of false prophets dividing the church today? How does Scripture equip believers to recognize and resist counterfeit messengers from God? Rodgers Atwebembeire of ACFAR explores these questions and many more in this wide-ranging interview.
free